Mapping the Distribution of Sea Surface Temperature and Chlorophyll-a in the Waters of Pieh Island Conservation Area Using Aqua MODIS Satellite Imagery - Maatitawaer, Natasya Debora Christiani; Rizvi, Fharisa Nabila; Kurniati, Fitri (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
Pieh Island Conservation Area is a conservation area that has abundant biodiversity, including coral reefs, turtles, whales, dolphins, and others. This study aims to determine the Mapping of Sea Surface Temperature Distribution and chlorophyll-A in the Pieh Island Conservation Area Waters Using AQUA MODIS Satellite Imagery. The methods used are active participation, literature study, and discussion with field supervisors in the Pieh Island Marine Conservation Area, West Sumatra Province. The results of the Thematic Internship Program MBKM with the title Mapping the Distribution of Sea Surface Temperature and Chlorophyll-A in the Waters of Pieh Island Conservation Area Using Aqua MODIS Satellite Imagery. Based on the graph, the average sea surface temperature and chlorophyll-a concentration in the Pieh Island Waters Conservation Area show that the highest sea surface temperature during 2023 is in February at 30 ° C, which continues to decrease to the lowest value in May. Then it increases again from June to August, respectively 27.5°C, 27°C, and 27.5°C, and then drops in September by 27.5°C. Furthermore, the chlorophyll-a concentration value has the lowest value in April with a value of 0.182 mg/m3and the highest peak is in August with a value of 0.362 mg/m3, The results of the correlation test between sea surface temperature and chlorophyll-a show a significance value of 0.152 which is greater than the general significance level of 0.05. Therefore, based on the statistical significance criterion, it cannot be ignored that there is no significant influence between the two variables. At the same time, however, the Pearson correlation value is -0.519, which reflects the negative relationship between sea surface temperature and chlorophyll-a.